Evaluation of the metal(loid)s phytoextraction potential of wild plants grown in three antimony mines in southern China. Issue 8 (3rd July 2021) - Zhang, Yunxia; Song, Bo; Zhu, Liangliang; Zhou, Ziyang
Abstract: Wild plant species from three deserted antimony (Sb) mine areas in southern China were collected to measure eight metal(loid)s. Antimony, As (arsenic), Cd (cadmium), Cr (chromium), Cu (copper), Ni (nickel), Pb (lead), and Zn (zinc) concentrations in plants and soil were analyzed. The soils of the mining area was weakly alkaline and contained toxic levels of Sb, As, Pb, Cd, and Zn. Many plant species in the area (40 species and 19 families) have no clear signs of toxicity. The plants were divided into three categories (high, moderate, and low tendency to accumulate metals) based on their (ratio [RT], bioaccumulation factor [BCF], translocation factor [TF]) values. The plants with a high accumulation tendency exhibited the high potential to absorb Sb from contaminated soil; therefore, they can be used for the remediation or phytoremediation of Sb-contaminated soil.